Indonesian Patients' Revisit Intention to Singapore Hospitals - Vinelya Tan; Renza Fahlevi; Fitriana Aidnilla Sinambela (Universitas Teknologi Yogyakarta, 2026)
Medical tourism has become one of the most dynamic sectors within the global tourism industry, particularly in Asia. Singapore has emerged as a leading medical tourism destination due to its advanced medical infrastructure, internationally accredited healthcare professionals, strong regulatory framework, and high standards of safety and security. Indonesian patients constitute one of the largest contributors seeking treatment in Singapore, driven by trust in service quality and perceived reliability of healthcare outcomes. This study investigates the influence of safety and security, price reasonableness, and word-of-mouth communication on medical tourism destination image and examines its effect on revisit intention among Indonesian patients. A quantitative research design was employed, with data collected through an online questionnaire targeting individuals who had previously received medical treatment in Singapore. The data were analyzed using SmartPLS through measurement and structural model evaluations. Results show that a positive destination image strongly predicts revisit intention, and that all three external elements have a significant positive effect on destination image. These findings emphasize the importance of developing a trustworthy, secure, and competitively priced medical environment to foster patient loyalty. The study also recommends future research to incorporate additional mediating variables such as trust, perceived medical service quality, and patient motivation to improve the robustness of the model.